2023
DOI: 10.3389/fimmu.2023.1130593
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with Tp0954, an adhesin of Treponema pallidum, provides protective efficacy in the rabbit model of experimental syphilis

Abstract: Syphilis, a chronic multisystemic disease caused by spirochete Treponema pallidum subspecies pallidum infection, continues to be a serious global health problem and congenital syphilis remains a major cause of adverse outcomes in pregnancy in developing countries. The development of an effective vaccine is the most cost-effective way to eliminate syphilis, but so far has been elusive. Here, we evaluated the immunogenicity and protective efficacy of Tp0954, a T. pallidum placental adhesin, as a potential vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The latest field of molecular biology and bioinformatics provides unprecedented opportunities for the identification of new vaccine targets. Several adhesins, such as TP0136 ( 142 ), TP0751 ( 143 ), and TP0954 ( 144 ), have been identified as major vaccine candidates, highlighting their role in invasion and dissemination of T. pallidum . Current limitations of these candidates include the requirement of extremely high doses, lack of cross-protection and potential side effects of adjuvants ( 142 , 144 ).…”
Section: Prevention Of Neurosyphilismentioning
confidence: 99%
See 1 more Smart Citation
“…The latest field of molecular biology and bioinformatics provides unprecedented opportunities for the identification of new vaccine targets. Several adhesins, such as TP0136 ( 142 ), TP0751 ( 143 ), and TP0954 ( 144 ), have been identified as major vaccine candidates, highlighting their role in invasion and dissemination of T. pallidum . Current limitations of these candidates include the requirement of extremely high doses, lack of cross-protection and potential side effects of adjuvants ( 142 , 144 ).…”
Section: Prevention Of Neurosyphilismentioning
confidence: 99%
“…Several adhesins, such as TP0136 ( 142 ), TP0751 ( 143 ), and TP0954 ( 144 ), have been identified as major vaccine candidates, highlighting their role in invasion and dissemination of T. pallidum . Current limitations of these candidates include the requirement of extremely high doses, lack of cross-protection and potential side effects of adjuvants ( 142 , 144 ). Although some scientists have attempted multicomponent vaccines, complete protection against infection has not yet been achieved ( 137 ).…”
Section: Prevention Of Neurosyphilismentioning
confidence: 99%
“…Mannose-modified lipid calcium phosphate nanoparticle vaccine is a novel tumor immunotherapy method that can enhance the immune response to tumors by regulating the tumor microenvironment [213]. Studies [214][215][216][217][218][219][220] have shown that the vaccine can activate the body's immune system, promote the expression and recognition of tumor-associated antigens, and trigger a specific immune response against tumor cells.…”
Section: Enhancement Of Tumor Immune Response and Establishment Of Im...mentioning
confidence: 99%